DAMPAK PENANAMAN MODAL DALAM NEGERI DAN ASING TERHADAP PERTUMBUHAN EKONOMI - Irfan Irfan; Herman Sjahruddin; Muhammad Ansaryandi; Hasrie Ainun Ramli; Fryson Fryson; Wahyu Pratama (LP2M Universitas Bina Bangsa, 2023)
This study examines the impact of domestic and foreign investment on economic growth in Indonesia, with the aim of understanding the factors that contribute to economic development. Economic growth is crucial for the progress of a region, but global economic growth has been disrupted by the COVID-19 pandemic. Investment serves as a catalyst for economic growth, and this study focuses on the effects of domestic and foreign investment on economic growth in Indonesia. The research method used is correlational research with a quantitative approach. The variables analyzed include domestic investment, foreign investment, and economic growth. Secondary data from the Central Bureau of Statistics spanning from 2020 to 2022 are utilized for the analysis. The data is analyzed through multiple panel data regression methods, using t-tests and classical assumptions. The results from the analysis show a significant positive effect between Domestic Investment and Foreign Investment on Economic Growth in Indonesia